OPN‐Mediated Crosstalk Between Hepatocyte E4BP4 and Hepatic Stellate Cells Promotes MASH‐Associated Liver Fibrosis - Sujuan Wang; Jiashi Gao; Meichan Yang; Gary Zhang; Lei Yin; Xin Tong (Advanced Science)
Abstract Stressed hepatocytes promote liver fibrosis through communications with hepatic stellate cells (HSCs) during chronic liver injury. However, intra‐hepatocyte players that facilitate such cell‐to‐cell communications are largely undefined. It is previously reported that hepatocyte E4BP4 is potently induced by ER stress and hepatocyte deletion of E4bp4 protects mice from high‐fat diet‐induced liver steatosis. Here how hepatocyte E4bp4 deficiency impacts the activation of HSCs and the progression toward MASH‐associated liver fibrosis is examined. Hepatic E4BP4 is increased in mouse models of NASH diet‐ or CCl4‐induced liver fibrosis. Hepatocyte‐specific E4bp4 deletion protected mice against NASH diet‐induced liver injury, inflammation, and fibrosis without impacting liver steatosis. Hepatocyte E4BP4 overexpression activated HSCs in a medium transfer experiment, whereas hepatocyte E4bp4 depletion did the opposite. RNA‐Seq analysis identified the pro‐fibrogenic factor OPN as a critical target of E4BP4 within hepatocytes. Antibody neutralization or shRNA depletion of Opn abrogated hepatocyte E4BP4‐induced HSC activation. E4BP4 interacted with and stabilized YAP, an established activator of OPN. Loss of hepatic Yap blocked OPN induction in the liver of Ad‐E4bp4‐injected mice. Hepatocyte E4BP4 induces OPN via YAP to activate HSCs and promote liver fibrosis during diet‐induced MASH. Inhibition of the hepatocyte E4BP4‐OPN pathway could offer a novel therapeutic avenue for treating MASLD/MASH.